IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL ASSISTED BY COMPUTER SIMULATION TOWARDS STUDENT’S CHARACTERS - Mariati Purnama Simanjutak; Juniar Hutahaean; Rika Indah Lestari; Primadana Barus (Universitas Negeri Medan, 2019)
The measure of success in education is not only assesed on the cognitive side, but also on the character side. Every students must have characters that adheres to the noble values of Indonesia. This research aims to know applied Problem Based Learning (PBL) model assisted by computer simulation with the increase of students character. This research used quasi experiment methode. The subject of this research involved three groups with each experimental group-1 that applying PBL assisted by computer simulation, the experimental group-2 applying PBL and the control group applying conventional models. The instrument of this study was a obeservation sheets and a questionnairies that measured student’s character. The character aspects that measured in this research were self-convidence, curiosity, planned, initiative, integrity, perseverance, problem solving, and teamwork. The character’s data analyzed with gain Test (N-gain). The increase percentage of N-gain of student’s character in experiment group 1 and experiment group 2 were 34% and 32% and respectively in medium category, but in control group, the increase was 12% , in the low category. The highest percentage increase in character of the experimental group 1 and experiment group 2 is the curiosity and the highest percentage increase in character of the control grou percentage increase in character of the is perseverance. Based on the results of the test, the application of pbl assisted by computer simulation is effective in improving student characters.